Produção de embriões em ovinos Morada Nova e Somalis Brasileira - Brasil, Oscar Oliveira (2016)
Superovulatory response and embryo yield in 19 Morada Nova and 20 Somalis Brasileira ewes was analyzed. All animals were synchronized with the insertion of an intravaginal device (CIDR(r)) on Day 0, replaced by a new device on Day 7, which remained in place until Day 14 and superovulated with 133mg of porcine FSH (pFSH) in decreasing doses at 12h intervals from Day 12 until Day 15 of the treatment, and a single dose of equine chorionic gonadotropin (eCG, 200UI) on Day 14 (i.e., administered in CIDR removal). Fifty hours after CIDR(r) removal, females were inseminated by laparoscopy. All embryos were recovered by laparotomy 5 days after insemination. Sheep which responded to the superovulation protocol (P>0.05) included 74% of the Morada Nova ewes and 50% of the Somalis Brasileira ewes. Morada Nova showed better results (P<0.05) than Somalis Brasileira in number of ovulations (15.38 ± 5.24 vs. 10.56 ± 2.83), total structures (11.00 ± 7.55 vs. 3.33 ± 1.94) and embryo yields (6.79 ± 5.35 vs. 2.90 ± 2.18). Despite the high fertilization rate, degenerate embryo rate was high for both breeds, with an overall rate of 39% (57/145). In conclusion, superovulatory response and embryo yields in Morada Nova ewes were considered sufficient to justify the use of this procedure in genetic resources conservation programs. However, improvements to embryo quality and control of precocious regression of corpus luteum are necessary to produce better results in the MOET program, with minimal variations and maximum embryo yield in Morada Nova and Somalis Brasileira ewes.